The importance of asset maximisation in football: Towards the long-term gestation and maintenance of sustained high performance - Gilmore, S. (International Journal of Sports Science and Coaching, 2009)
Based upon an extended case study of Bolton Wanderers Football Club, this article argues that asset management strategies need to be accompanied by human resource management (HRM) practices capable of identifying, attracting, developing and retaining strategically valuable staff (as well as skilled players) with the requisite knowledge and abilities to enact asset maximization plans. The article concludes with a range of recommendations for consideration by the strategic apex of the football department, focusing on the role of HRM in creating and maintaining these approaches to securing sustained performance.